1987
DOI: 10.2307/3576889
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Alkaline Phosphatase Activity Loss as an Early Stage in the Development of Radiation-Induced Heart Disease in Rats

Abstract: Alkaline phosphatase activity of capillary endothelial cells in the heart of Wistar and Sprague-Dawley rats was studied sequentially after single doses of 10, 15, 20, or 25 Gy. Following irradiation capillary density and alkaline phosphatase activity were focally lost before myocardial degeneration or clinical symptoms of heart disease developed. Recovery from both changes took place after doses of 10 or 15 Gy. The decrease in capillary density and enzyme activity showed the same strain difference in latency t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 9 publications
5
38
0
2
Order By: Relevance
“…Simultaneous with capillary rarefication is a focal loss of the endothelial cell marker enzyme alkaline phosphatase that increases with time. When the foci of myocardial degeneration developed, they were invariably situated within the areas of enzyme loss [9,25] . Loss of enzyme activity was associated with foci of myocardial degeneration, supporting the hypothesis that lesions were secondary to vascular endothelial cells injury [9] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneous with capillary rarefication is a focal loss of the endothelial cell marker enzyme alkaline phosphatase that increases with time. When the foci of myocardial degeneration developed, they were invariably situated within the areas of enzyme loss [9,25] . Loss of enzyme activity was associated with foci of myocardial degeneration, supporting the hypothesis that lesions were secondary to vascular endothelial cells injury [9] .…”
Section: Discussionmentioning
confidence: 99%
“…There is compelling epidemiological evidence that the risk of dying from myocardial infarction or another ischemic heart disease is significantly increased at more than 10−15 years after exposure of the heart to local irradiation [7] . Radiation-induced damage to the microvasculature has severe pathological implications for kidney, heart and other tissues [8][9][10] . The most significant type of radiation-induced heart disease (RIHD) appears to be myocardial damage, which may result from loss of alkaline phosphatase activity of capillary endothelial cells 6−10 weeks after radiotherapy [9,11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation-induced damage to the microvasculature plays an important part in the pathology of different normal tissues such as kidney and heart (6,14,15). It has been proposed that effective pharmacological intervention to protect the vascular system, especially the endothelial cells, could lead to a decrease in normal tissue damage.…”
Section: Original Articlementioning
confidence: 99%
“…It suggested that an non-liner dose-response relationship existed between radiation and atherosclerosis, that is also to say a protective effect on cardiovascular in very-low-dose occupational exposures (0.02 Sv), but detrimental effects in higher doses (0.2 Sv) in epidemiological researches [34]. After low-dose radiation, the earliest morphological changes in the irradiated heart were lymphocyte adhesion and extravasation, thereby causing changes in the function of capillary endothelial cells and leading to thrombosis, microvascular obstruction, and decreased capillary density, accompanied by loss of endothelial cell markers of alkaline phosphatase [35][36][37]. Increased proliferation ability of the remaining capillary endothelial cells is not sufficient to maintain proper microvascular function and therefore led to ischemia, myocardial cell death, and fibrosis [38].…”
Section: Molecular Mechanismsmentioning
confidence: 99%